PENGARUH LITERASI KEUANGAN DAN INKLUSI KEUANGAN TERHADAP KETAHANAN KEUANGAN MENGGUNAKAN PERILAKU KEUANGAN SEBAGAI VARIABEL INTERVENING PELAKU USAHA CATERING SELAMA PANDEMI COVID-19 - Frendy Astra (2022)
This study aims to examine the effect of financial literacy, financial inclusion on financial resilience with financial behavior as an intervening variable for catering business actors during the Covid-19 pandemic. The population in this study is catering business actors in the DKI Jakarta area and its surroundings. The sample was selected based on the multistage random sampling technique. In this study using primary data consisting of questionnaires and interviews. The results showed that financial literacy had a positive and significant effect on financial resilience with financial behavior as partial mediation, financial inclusion had a positive and significant effect on financial resilience with financial behavior as partial mediation.